STUDI KASUS TENTANG PESERTA DIDIK YANG SULIT MENGENDALIKAN EMOSI PADA KELAS VIII SMP NEGERI 14 PONTIANAK - Luthfia, Fajriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research entitled case study about students who are difficult to control emotion in class VIII SMP Negeri 14 Pontianak.The general problem in this research is how to help learners who are difficult to control emotion in class VIII SMP Negeri 14 Pontianak. While the objective is to obtain an objective picture of the characteristics, factors causing, and appropriate alternative assistance to be used in overcoming the problems of students who are difficult to control emotions in class VIII SMP Negeri 14 Pontianak. The approach used in this research is qualitative by using descriptive method and the form of research is case study. There are two case subjects in this study, the alternative aid given to the first subject is in the form of treatment using conceptual modeling techniques so that the behavioral of the subject can shape new behavioral better. While alternative assistance is given to the second, the case subject is treatment by using directive techniques in the RET counseling model so that case subjects can change their irrational mindset into a rational mindset. Keywords: Difficult to Control Emotions, Behavioral Counseling, RET Counseling